2012
DOI: 10.5194/angeo-30-1025-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of rolled up Kelvin-Helmholtz vortices at Earth's dayside and flank magnetopause

Abstract: Abstract. The Kelvin-Helmholtz Instability (KHI) can drive waves at the magnetopause. These waves can grow to form rolled-up vortices and facilitate transfer of plasma into the magnetosphere. To investigate the persistence and frequency of such waves at the magnetopause we have carried out a survey of all Double Star 1 magnetopause crossings, using a combination of ion and magnetic field measurements. Using criteria originally used in a Geotail study made by Hasegawa et al. (2006) (forthwith referred to as H20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 56 publications
5
70
0
Order By: Relevance
“…For example, toroidal mode plasma waves on the dawn side of the magnetosphere, as reported by Anderson et al 23 and Takahashi et al 24 , have been attributed to the KHI. On the other hand, Taylor et al 25 have suggested that the KHI is more prevalent around dusk, which is in agreement with observations of Mercury. Global simulations similar to those performed by Claudpierre et al 26 , but incorporating northward (rather than southward), IMF can potentially answer questions about asymmetry at Earth.…”
Section: Discussionsupporting
confidence: 88%
“…For example, toroidal mode plasma waves on the dawn side of the magnetosphere, as reported by Anderson et al 23 and Takahashi et al 24 , have been attributed to the KHI. On the other hand, Taylor et al 25 have suggested that the KHI is more prevalent around dusk, which is in agreement with observations of Mercury. Global simulations similar to those performed by Claudpierre et al 26 , but incorporating northward (rather than southward), IMF can potentially answer questions about asymmetry at Earth.…”
Section: Discussionsupporting
confidence: 88%
“…This result also took into account the faster magnetosheath flow (and enhanced velocity shear) on the dusk-flank (Longmore et al, 2005;Walsh et al, 2012;Dimmock and Nykyri, 2013) during these conditions. Interestingly, Taylor et al (2012) reported Cluster observations showing that the occurrence of the KHI was larger on the dusk-flank when observations were limited to the dayside. The results of Nykyri (2013) are relevant close to the terminator and on the nightside.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…next paragraph), and their intermittent observation may be due to small-scale changes in the distance from the magnetopause to the spacecraft not accounted for in the MHD simulation. The reader is referred to Lavraud and Borovsky [2008] for aspects related to enhanced flows and associated magnetopause wave activity during low M A (see also Chen et al [1993], Lavraud et al [2009] and Taylor et al [2012]). However, this topic is beyond the focus of the present study.…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%